IMPLEMENTASI PARTISIPASI PUBLIK DALAM PENYUSUNAN UNDANG-UNDANG DI DPR RI STUDI KASUS: PENYUSUNAN UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KUHP - Sari Yuliati; I Dewa Ayu Widyani; Situmeang, Tomson; Jimmy Simanjuntak (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
DPR RI has the authority to cover three functions, namely the budget function, supervisory function and legislative function. Legal products or laws are drafted through a formation process with meaningful participation by the public, as stipulated in Law Number 12 of 2011 as amended by Law Number 13 of 2022 on the Formation of Legislation (PPP Law). In drafting the Criminal Code Law, the House of Representatives certainly adheres to the PPP Law as a guideline. Through this research, it attempts to analyze the drafting process and the formation of Law No. 1 of 2023 on the Criminal Code with reference to the PPP Law. This research uses normative research method with statute approach and conceptual approach. The scope of this research is to examine meaningful public participation in the preparation or formation of Law No. 1 of 2023 on the Criminal Code. The findings of this study, although a series of processes have been carried out in the preparation of Law Number 1 Year 2023 on the Criminal Code, there are still debates in the community that cannot escape criticism as a form of public participation.